The writer's way - Rawlins, Jack 1946- (Wadsworth, 2012)
Writers learn best when inspired by compelling reasons to write, aided by examples and reinforced by immediate personal rewards. With sound advice offered in a supportive tone, this book leads you through the writing process, from the importance of understanding your audience to pre-writing to polishing the final draft. You'll learn why good writers ask of their writing, "Will this work?" You'll also learn how to ensure that - with practice and revision - your answer will be "yes."--COVER.